Channel Modeling for Multi-Receiver Molecular Communication System by Impulsive Force in Internet of Nano Things - Pengfei Zhang; Pengfei Lu; Xuening Liao; Xiaofang Wang; Ping Zhou (Sensors)
When studying molecular communication (MC) systems within fluid environments of the Internet of Nano Things (IoNT), fluid resistance has a significant impact on molecular transmission characteristics. In single-input multiple-output (SIMO) scenarios with multiple receivers, the interaction between fluid effects and inter-receiver interference complicates the modeling process. To address these challenges, this paper incorporates fluid resistance into a three-dimensional SIMO model and investigates the impact of the angle between receivers and the direction of the molecular pulse—considering both azimuth and polar angles—on the number of molecules received. Additionally, the interference from other receivers on the primary receiver is analyzed, and a mathematical expression for the number of received molecules is derived. Simulation results validate the model’s accuracy. The experiments show that as the distance between the interfering receiver and the transmitter increases from 0.10 m to 0.95 m, the number of molecules received by the primary receiver first rises and then falls, exhibiting a nonlinear interference pattern. Moreover, reception efficiency peaks when the receiver is positioned at a polar angle of 90° and an azimuth of 0°, with deviations from these angles leading to performance degradation. The spatial arrangement of receivers and transmitters, the number of receivers, and the initial velocity of molecules all significantly influence reception performance.